Enhancing E-Insurance Mobile Applications through Cognitive Walkthrough and System Usability Scale (SUS): A Case Study of My Taspen Life - Diarto , Nur; Santoso, Harry Budi (Indonesian Scientific Journal, 2026)
The digital transformation of the insurance sector has necessitated mobile services with superior usability. The My Taspen Life mobile application has experienced low user satisfaction attributed to its suboptimal user interface (UI) and user experience (UX). This study aimed to evaluate the application's usability and propose a validated high-fidelity prototype employing a User-Centered Design (UCD) approach. A mixed-methods evaluation comprised a System Usability Scale (SUS) survey, a Cognitive Walkthrough with experts, and Usability Testing. The identified issues were mapped against Shneiderman’s Eight Golden Rules of Interface Design to develop an adequate solution. The initial results showed an average SUS score of 65.51, below the global SUS average, and identified critical constraints in layout, navigation, and visual representation. Following the redesign, the prototype was re-evaluated by 12 participants, equally distributed between employees and external users. The final evaluation demonstrated a significant improvement, achieving a SUS score of 83.54 (Grade A,